2007
DOI: 10.1007/s11259-007-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Subclinical Ketosis in Dairy Herds in Iran

Abstract: Subclinical ketosis (SCK) is defined as elevated concentrations of ketone bodies in the absence of clinical signs of ketosis. It is an important metabolic disease in dairy cattle during early lactation and is associated with losses in milk production and several other periparturient diseases. Limited information is available regarding the prevalence of SCK in dairy herds in Iran. The objectives of this study were (i) to determine the incidence of SCK in the dairy herds in Kerman province of Iran using serum be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Cut‐points used to identify subclinical ketosis have ranged from 1.0 to 1.4 mmol/L for blood, serum and plasma BHB concentrations . The prevalence of subclinical ketosis was high in the current population of cattle, with 20% having a serum BHB ≥ 1.4 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Cut‐points used to identify subclinical ketosis have ranged from 1.0 to 1.4 mmol/L for blood, serum and plasma BHB concentrations . The prevalence of subclinical ketosis was high in the current population of cattle, with 20% having a serum BHB ≥ 1.4 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Sakha et al (2007) reported lower serum glucose concentrations for cows with sub-clinical ketosis than healthy cows, whereas other researchers observed no association between glucose in blood and risk of disease (i.e., LDA and ketosis) and culling during the postpartal period (Stengärde et al, 2010;Seifi et al, 2011). In the present study, the development of sub-clinical diseases was not evaluated and the incidence of LDA and clinical ketosis was low due to our strict focus on the development of primary diseases during early lactation (i.e., not the development of a disease as a secondary health problem).…”
Section: Metritismentioning
confidence: 99%
“…The threshold values for BHBA in serum or plasma of cows suffering from SCK has been defined either as 1.2 mmol/L or 1.4 mmol by different researchers [6,14,16,17,19]. The proportion of cows diagnosed with SCK was lower in this study compared to others [2,16,21,23] which showed that SCK was not a serious problem in the farms studied.…”
Section: Discussionmentioning
confidence: 58%
“…The gold standard diagnostic test for SCK is measuring BHBA concentration in serum or plasma because it is stable [13,17,18]. Threshold values of either 1.2 mmol/L [19,20] or 1.4 mmol/L [6,12,16,17] of BHBA in serum or plasma have been recommended to distinguish between normal and cows suffering from SCK. Measuring serum concentration of BHBA is useful for examining individual cows, evaluating herd health and monitoring feeding management [21].…”
Section: Introductionmentioning
confidence: 99%